PRIMARY LYMPHOMA OF THE CENTRAL NERVOUS SYSTEM WITH DAMAGE TO THE ROOTS OF THE PONYTAI - Светлана Алексеевна Зуева; Валентина Львовна Юрманова; Юрий Михайлович Портнов; Валерия Викторовна Романова; Виталий Николаевич Речкин; Владимир Александрович Семенов; Светлана Ивановна Елгина; Вадим Гельевич Мозес; Елена Владимировна Рудаева; Кира Борисовна Мозес (Медицина в Кузбассе)
Primary lymphoma of the central nervous system (PLCNS) is a rare form of non-Hodgkin's extranodal lymphomas (NHL) with isolated damage to the brain, its membranes, spinal cord or eyes with specific neurological manifestations without signs of systemic involvement with a frequency of 4-7 cases per 1000000 population. A clinical case of PLCNS in an 18-year-old patient with a disease duration of 6 months with an extremely rare manifestation of the manifestation of symptoms of the disease with damage to the structures of the horse tail of the spinal cord is presented.